The role of microbial fertilizers in diversified cropping systems - Romero-Figueiras, Tania; Andrés-Meza, Pablo; Murguía-González, Joaquín; Espinosa-Calderón, Alejandro; Maldonado-Saavedra, Octavio; Leyva-Ovalle, Otto Raúl (Ecosistemas y Recursos Agropecuarios, 2024)
Agroforestry systems combine fruit trees with crops, providing environmental and productive benefits. This study investigated the impact of a combined application of arbuscular mycorrhizal fungi (AMF), Rhizobium, and mineral fertilization levels on the agronomic and physiological characteristics of maize (Zea mays L.) and common bean (Phaseolus vulgaris L.) intercropped with peach (Prunus persica), Persian lime (Citrus latifolia Tan.), and litchi (Litchi chinensis). The study also examined changes in the physical, chemical, and microbiological properties of the soil. An agroforestry system was established during the fall-winter agricultural cycle of 2020 in the community of Campo Grande, municipality of Ixtaczoquitlan, Veracruz, Mexico. The treatment with Rhizophagus irregularis + Rhizobium etli (2) + 50% mineral fertilization produced the greatest increases in plant height: 68.5±8.6 cm (Persian lemon), 105.3±11.0 cm (peach) and 6.8±4.5 cm (lychee). It also produced the highest grain yield in corn (5 653.7 kg ha-1) intercropped with beans (995.1 kg ha-1). At the end of the first productive cycle, the soil pH decreased from moderately acidic (5.7) to acidic (4.9). On the other hand, the organic matter increased from 1.71 to 2.76%. There was an increase in the number of bacteria (55.0 x 106 to 68.0 x 106 CFU g-1 soil), fungi (73.55 x 102 to 511.7 x 102 CFU g-1 soil) and actinomycetes (48.61 x 105 to 53.19 x 105 CFU g-1 soil). The establishment of diversified agricultural systems in combination with microbial consortia promotes crop productivity and improves the physical, chemical, and microbiological properties of the soil.
Keywords: milpa system; fruit trees; soil health; microbial consortia; productivity